Structure‐Making Effects of Metal Nanoparticles in Amyloid Peptide Fibrillation. (15th December 2014) - Gladytz, Anika; Wagner, Maximilian; Häupl, Tilmann; Elsner, Christian; Abel, Bernd
<x xml:space="preserve">Abstract</x> There is growing concern that nanoparticles (NPs) may accelerate amyloid protein aggregation and thus cause amyloid‐related diseases. Here, the potential of silver and gold NPs is explored (diameter 20 nm) on the aggregation of the amyloid peptide sequences NNFGAIL from human islet amyloid polypeptide and the yeast prion protein sequence GNNQQNY, which are both the sequences of the full systems, which are able to aggregate into characteristic amyloid cross‐beta sheet fibrillar structures. Here, it is shown that silver and gold NPs in physiological aqueous solution at ambient temperatures accelerate the aggregation kinetics of both peptides significantly (in vitro). Scanning electron microscopy and X‐ray diffraction provide solid evidence for a "structure‐making" effect of the NPs. In particular, we are able to image the initial peptide corona and measure its structural reorganization in time‐resolved kinetic experiments. After a conversion time Δt, the coated NPs appear to act as templates or seeds for rapid fibrillation. Interestingly, cross‐fibrillation experiments with different peptide‐coated NPs (pcNPs) reveal that they can efficiently induce aggregation of similar peptides once the pcNPs are structurally converted. It is discussed that these structurally converted pcNPs may display similar kinetic features as toxic and aggregation inducing oligomers/protofibrils in normal amyloid aggregation, without being transient and very low‐concentration species. Finally, we suggest and discuss a simple mechanistic picture with the biomolecule corona of NPs being central to the function of the coated NPs in amyloid fibrillation.